Side-of-Implantation Effect on Functional Asymmetry in the Auditory Cortex of Single-Sided Deaf Cochlear-Implant Users - Anna Weglage; Verena Müller; Natalie Layer; Khaled H. A. Abdel-Latif; Ruth Lang-Roth; Martin Walger; Pascale Sandmann (Brain Topography, 2022)
Cochlear implants (CIs) allow to restore the hearing function in profoundly deaf individuals. Due to the degradation of the stimulus by CI signal processing, implanted individuals with single-sided deafness (SSD) have the specific challenge that the input highly differs between their ears. The present study compared normal-hearing (NH) listeners (N = 10) and left- and right-ear implanted SSD CI users (N = 10 left, N = 9 right), to evaluate cortical speech processing between CI- and NH-ears and to explore for side-of-implantation effects. The participants performed a two-deviant oddball task, separately with the left and the right ear. Auditory event-related potentials (ERPs) in response to syllables were compared between proficient and non-proficient CI users, as well as between CI and NH ears. The effect of the side of implantation was analysed on the sensor and the source level. CI proficiency could be distinguished based on the ERP amplitudes of the N1 and the P3b. Moreover, syllable processing via the CI ear, when compared to the NH ear, resulted in attenuated and delayed ERPs. In addition, the left-ear implanted SSD CI users revealed an enhanced functional asymmetry in the auditory cortex than right-ear implanted SSD CI users, regardless of whether the syllables were perceived via the CI or the NH ear. Our findings reveal that speech-discrimination proficiency in SSD CI users can be assessed by N1 and P3b ERPs. The results contribute to a better understanding of the rehabilitation success in SSD CI users by showing that cortical speech processing in SSD CI users is affected by CI-related stimulus degradation and experience-related functional changes in the auditory cortex.

Thalamic and basal ganglia regions are involved in attentional processing of behaviorally significant events: evidence from simultaneous depth and scalp EEG - Anne-Kathrin Beck; Götz Lütjens; Kerstin Schwabe; Reinhard Dengler; Joachim K. Krauss; Pascale Sandmann (Brain Structure and Function, 2018)

Association of Concurrent fNIRS and EEG Signatures in Response to Auditory and Visual Stimuli - Ling-Chia Chen; Pascale Sandmann; Jeremy D. Thorne; Christoph S. Herrmann; Stefan Debener (Brain Topography, 2015)

Source Localisation of Visual Evoked Potentials in Congenitally Deaf Individuals - Nadine Hauthal; Jeremy D. Thorne; Stefan Debener; Pascale Sandmann (Brain Topography, 2014)

Excitability changes induced in the human auditory cortex by transcranial direct current stimulation: direct electrophysiological evidence - Tino Zaehle; Manuela Beretta; Lutz Jäncke; Christoph S. Herrmann; Pascale Sandmann (Experimental Brain Research, 2011)